MYC target gene activation in chronic lymphocytic leukemia and richter transformation: links to aggressiveness and tumor microenvironment interactions - M. Tsagiopoulou; S. Rashmi; M. Chatziaslani; M. Chatziaslani; M. Chatziaslani; I. Gut; I. Gut (Frontiers in Pharmacology)
Chronic Lymphocytic Leukemia (CLL) is characterized by clinical and biological heterogeneity, with a subset of patients progressing to Richter Transformation (RT), an aggressive lymphoma. This study explores MYC target gene activation across various CLL stages and disease subgroups using bulk RNAseq and single-cell RNAseq data. Our findings reveal increased MYC activation in unmutated IGHV CLLs, trisomy 12 cases, and RT stages. In RT, MYC activation is independent of B-cell receptor signaling, correlating instead with cell cycling and TLR9 interactions, indicating alternative survival mechanisms. High MYC activation correlates with shorter time to first treatment and enhances tumor microenvironment interactions, particularly with myeloid cells. These results underscore MYC’s significant role in CLL progression and RT, supporting MYC’s potential as a target for stratifying CLL patients and developing therapeutic strategies.